Innovations and Emerging Technologies in Wound Care 2020
DOI: 10.1016/b978-0-12-815028-3.00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Lower leg compression and its biomechanical effects on the soft tissues of the leg

Abstract: Elastic compression of the lower leg is the traditional preventive and curative treatment of venous insufficiency. After presenting the medical strategies related to compression therapies, this chapter develops current advances in clinics as well as in engineering and outline the more important knowledge arising from this review. Compression hosiery acts by providing pressure to the leg. Pressure generation using socks mainly depends on the stiffness and the size of the socks, the size of the leg, but also the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Compression stockings are known as the first line treatments to manage varicose veins and treat them at initial stage without healing or venous ulceration of legs. It was observed that compression stockings have an effective role in the field of health care and can treat symptoms of deep vein thrombosis (DVT) i.e., initial stage treatment of the varicose diseases 5 . The prevalence of this disease is almost 5% to 45% in adults and is a multi-factorial disease involving positive family history, pregnancy, lifestyle, smoking, obesity and standing long hours at work 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Compression stockings are known as the first line treatments to manage varicose veins and treat them at initial stage without healing or venous ulceration of legs. It was observed that compression stockings have an effective role in the field of health care and can treat symptoms of deep vein thrombosis (DVT) i.e., initial stage treatment of the varicose diseases 5 . The prevalence of this disease is almost 5% to 45% in adults and is a multi-factorial disease involving positive family history, pregnancy, lifestyle, smoking, obesity and standing long hours at work 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Wearing a graduated compression product delivers pressure from outside to the body to increase the hydrostatic pressure and redress the pressure balance between the deep and superficial veins to improve blood circulation in the lower limb [5]. In fact, the pressure of compression tights used for the prevention or treatment of cardiovascular diseases has been verified regarding their positive health effects [6].…”
Section: Introductionmentioning
confidence: 99%